Propaganda and persuasion: political discourse and the negotiation of power and authority in Yorkist and early Tudor England - Wheddon, Rebecca (2024)
The period 1471-1509 was one of the most tumultuous in English history. The fact that there were four different kings in thirteen years meant that the stability and authority of the English Crown were severely weakened. English kingship therefore had to adapt and discover new methods through which to negotiate and demonstrate its power and authority. One of the most significant of these was the use of propaganda and rhetoric, as the increased focus on public support and widening levels of literacy led to ever more emphasis on the importance of language. Using a language-based method of historical analysis, inspired by the ‘Linguistic Turn’ moment in historiography this thesis is the first in-depth examination of political language across an extended period of history. Its focus is on Edward IV, Richard III and Henry VII, and how they used propaganda and rhetoric to negotiate and project power and authority.